On neotypes and nomina nova: commentary on “Comparative analysis of Faecalibacterium prausnitzii genomes shows a high level of genome plasticity and warrants separation into new species-level taxa”, by C.B. Fitzgerald et al. (BMC Genomics (2018) 19:931) - Aharon Oren; George M. Garrity (BMC Genomics, 2020)
Abstract In their paper entitled “Comparative analysis of Faecalibacterium prausnitzii genomes shows a high level of genome plasticity and warrants separation into new species-level taxa” (BMC Genomics (2018) 19:931), Fitzgerald et al. proposed a neotype strain for F. prausnitzii (strain A2–165 = DSM 17677 = JCM 31915) and assigned strain ATCC 27768 = NCIMB 13872 to a newly established taxon, Faecalibacterium moorei nom. Nov. These proposals contravene the Rules of the International Code of Nomenclature of Prokaryotes (ICNP). Neotype strains can only be established following a formal proposal in the International Journal of Systematic and Evolutionary Microbiology in accordance with Rule 18c and Appendix 7 of the ICNP. A proposed neotype becomes an established neotype after 2 years, provided that no objections were submitted to the Judicial Commisson of the International Committee on Systematics of Prokaryotes within the first year following publication of the request. F. moorei as proposed by Fitzgerald et al. is a later homotypic synonym of F. prausnitzii. It cannot be a ‘nom. nov.’ (nomen novum): based on Rule 34a of the ICNP: this term is only used when an author transfers a species to another genus or a subspecies to another species as a new combination, but the original specific epithet cannot be used as ‘comb. nov.’ (combinatio nova) as a result of homonymy. Moreover, ATCC 27768 and NCIMB 13872 cannot be proposed as the type strain of F. moorei as these remain permanently associated with the type strain of F. prausnitzii unless the Judicial Commission of the ICSP will decide otherwise.